Pengaruh Kepemimpinan Transformasional dan Budaya Organisasi terhadap Kepuasan Kerja Karyawan PT. Tunas Ridean Jakarta - Zikri Bintang; Arief Syah Safrianto (Jurnal Manajemen Bisnis Krisnadwipayana, 2026)
The purpose to analyze the influence of transformational leadership and organizational culture on employee job satisfaction at PT. Tunas Ridean Jakarta. This research is included in the category of causal associative research using a quantitative approach. The population in this study were employees of PT. Tunas Ridean Jakarta. The technique used for sampling is simple random sampling. The analytical method uses simultaneous and partially linear regression analysis. The results of the research show that in simultaneous and partially ways transformational leadership and organizational culture have a positive and significant effect on job satisfaction at PT. Tunas Ridean Jakarta.